Algebra-Gleichungen-Exponentialgleichungen


  • $a b^{(cx+d)}+f=0 $
    1 2 3 4 5 6
    $a e^{(cx+d)}+f=0 $
    1 2 3 4

Beispiel Nr: 04
$ \text{Gegeben:}a e^{(cx+d)}+f=0 \\ \text{Basis: }e = 2,718.. (eulersche Zahl) \\ \\ \text{Gesucht: } \text{Lösung der Gleichung} \\ \\ a e^{(cx+d)}+f=0 \\ \textbf{Gegeben:} \\ a=4 \qquad c=5 \qquad d=-4 \qquad f=-4 \\ \\ \textbf{Rechnung:} \\ 4 \cdot e^{(5x-4)}-4 =0 \\ 4 \cdot e^{(5x-4)}-4=0 \qquad /+4 \\ 4 \cdot e^{(5x-4)}=+4 \qquad /:4 \\ e^{(5x-4)}=1 \qquad /\ln \\ 5x-4=\ln \left(1 \right) \qquad / +4 \qquad / :5 \\ x=\frac{4}{5} $